Impact of Physical Activity on Improving Bone Health in Adolescents : A Literature Study - Mappanyukki, Andi Atssam; Aksir, Muh Ilham; Hasyim, Hasyim (ILIN Education Indonesia, 2024)
This research uses the literature review method to analyze and synthesize information from various studies that have been conducted regarding the impact of physical activity on adolescent bone health. The data used in this study came from scientific journals, research articles, books, and reports published in the last 10 years. The data were retrieved from trusted academic platforms such as PubMed, ScienceDirect, Google Scholar, and national journal portals such as Garuda. Data were collected using specific keywords such as “benefits of physical activity for adolescent bones”, “bone and exercise”, and “adolescent bone health”. After the search, relevant articles were identified and selected based on predetermined inclusion and exclusion criteria. Data analysis was performed descriptively to summarize relevant research findings. In conclusion, this study highlights the importance of a holistic approach in supporting bone health. A combination of weight-based exercise, optimal nutrition and injury risk management strategies can provide maximum benefits. By considering individual differences, such as gender, health conditions, and physical activity preferences, appropriate intervention strategies can be implemented to support bone health throughout the life cycle.